Trace Elements Reconnaissance on the South Fork of Quartz Creek, Northeastern Seward Peninsula, Alaska - Killeen, P. L.; White, Max Gregg (Geological Survey (U.S.), 1950)
Abstract: Two uranium-bearing minerals, uranothorianite and thorite (?), were found in the stream gravels of the main branch of the South Fork of Quartz Creek, a tributary of the Kiwalik River. Although the bedrock source of the minerals was not located, the radioactive material was traced in slope wash well above the stream gravel. A detailed investigation of the area with more sensitive counters might reveal the source of the minerals and localities where the minerals are sufficiently concentrated to be minable.